Intake of Folic Acid During Pregnancy Correlates to Preeclampsia Incidents in Health Center of Surabaya - Putri Ulin Nuha; Bambang Purwanto; Rizki Pranadyan; Dwi Purwanti (Humanistic Network for Science and Technology (HNST), 2018)
Maternal Mortality Rate (MMR) in Indonesia based on 2015’s Health Profile of Indonesia has reached 305 per 100,000 live births. Preeclampsia is known being one of the most related factors of MMR Studies suggest that the use of folic acid may lower the risk of hypertensive disorders in pregnancy. It has been suggested that folic acid and Folic acid containing multivitamins may reduce the risk of preeclampsia by lowering plasma homocysteine concentrations in pregnant women. This cross sectional study aimed to analyze the correlation between intake of Folic acid with preeclampsia. Data was taken using Food Frequency Questionaire (FFQ) with semi quantitative approach by interviewing subjects. Sampling was obtained by simple random sampling with total 80 subjects. Data was analyzed using Chi square test. There were 15% of subjects diagnosed with preeclampsia and 83.3% of women with preeclampsia were deficient of Folic acid. Data analysis showed there is correlation between intake of Folic acid during pregnancy with preeclampsia in Sidotopo Wetan Health Care Centre (p= 0.028), while OR value was 0.158 (95% CI 0.032 to 0.776). It can be concluded that insufficient intake of Folic acid during pregnancy correlate to preeclampsia incidents. Keywords: Folic Acid, Preeclampsia, Incidents, Pregnancy